The successful use of the Impella RP after a long cardiopulmonary resuscitation and systemic thrombolytic therapy in a patient with a fulminant pulmonary embolism: the first case report. Issue 1 (12th January 2018) - Youssef, Akram; Selle, Anna; Ende, Georg; Ibrahim, Karim
Abstract: Acute massive pulmonary embolism (PE) can result in progressive cardiogenic shock, right heart failure, and respiratory failure requiring cardiopulmonary resuscitation (CPR). We report the case of a 56-year-old woman who required prolonged CPR secondary to a highly suspected massive PE and cardiogenic shock. After receiving preclinical thrombolytic therapy, the patient was transferred to the intensive care unit with ongoing CPR. Because of persistent haemodynamic instability and acute right ventricular failure, an Impella RP was successfully implanted and immediate haemodynamic improvement was observed. Absent any contraindications, the Impella RP should be considered a feasible alternative in patients with acute right ventricular failure due to pulmonary embolism.